Geographical gradient of genetic diversity of Deschampsіa antarctіca Desv. from the Maritime Antarctic - Andreev, I. O.; Volkov, R. A.; Kozeretska, I. A.; Parnikoza, I.Yu.; Spiridonova, K. V.; Kiryachenko, S. S.; Maydanyuk, D. N.; Kunakh, V. A. (Ukrainian Antarctic Journal, 2012)
In order to study the genetic diversity of D. antarctіca Desv. and phylogenetic relationships between the plants from Antarctica and outside of its borders RAPD-analysis and comparative sequence analysis of rDNA internal transcribed spacers 1 and 2 region (ITS1-2) were conducted. There are 15 samples were studied from two distant regions, namely from King George Island and from islands of Argentine archipelago region. The results of RAPD-analysis indicate the differentiation of the studied populations at the molecular genetic level and the existence of a geographical gradient of genetic diversity of D. antarctіca in Maritime Antarctica with a decrease in this parameter from north to south. Sequence analysis of the ITS1-2 rDNA region revealed the presence of several variants in Antarctic populations that differ by specific mutations from plants growing outside Antarctica.